Determining Canine Blood and Human Blood Composition by Congealing Microliter Drops into Homogeneous Thin Solid Films (HTSFs) via HemaDrop™. (11th July 2017) - Pershad, Yash; Herbots, Nicole; Day, Grady; van Haren, Ryan; Whaley, Shawn; Martinez, Alvaro; Suhartono, Sabrina; Culbertson, Robert; Mangus, Mark; Wilkens, Barry
ABSTRACT: Accurate analysis of microliter blood samples can improve patient care during medical testing and forensics. Patients can suffer from anemia due to the larger volume required for blood tests, 7 milliliters per vial. Attempts at analysis of nanoliter blood samples by Theranos have systematic errors > 10%, higher than medically acceptable thresholds. Our research aims to analyze composition of microliters of blood. This research investigates accuracy of analyzing blood via HemaDrop™, a patented technique to create a Homogenous Thin Solid Film (HTSF) on super-hydrophilic and hyper-hydrophilic surfaces with 5 microliter droplets of blood. To investigate HemaDrop™'s accuracy, Ion Beam Analysis (IBA) is conducted on dried blood spots (DBS) and HTSFs from congealed blood drops on HemaDrop™-treated samples. HTSFs are observed via optical microscopy to compare uniformity, precipitation, and phase separation. DBSs and HTSFs are compared via optical microscopy for canine blood and human blood. After drying uncoated samples, canine and human blood DBSs exhibit cratering, phase separation, and lack of uniformity. Conversely, HTSFs are uniform, exhibiting no cratering and little phase separation. Next, IBA demonstrates that HTSFs of canine and human blood solidified on super-hydrophilic and hyper-hydrophilic coatings yield spectra where species and electrolytes can be identified, unlike on DBSs. The damage curve method enables extracting accurate blood composition for elements, accounting for IBA damage. Relative error in blood elemental composition is within the 10% medical threshold. While both produced films within the 10% threshold, hyper-hydrophilic coatings eliminated phase separation from serum observed in HTSFs on super-hydrophilic coatings. HemaDrop™ provides consistent measurements independent of sample, showing HTSFs from µL blood drops are uniform, reproducible, and free of phase separation. Thus, HemaDrop™ allows for analysis in vacuum from congealed blood drops and expands the range of techniques to identify elements and molecules.